Indoor-season changes in the stabilometry of sprinters and middle-distance runners - Romero-Franco, N.; Martinez-López, E.J.; Hita-Contreras, F.; Martinez-Amat, A. (Science & Sports, 2015)
Objectives: The purpose of the present study is to analyze the stabilometric differences in every training period of the indoor-season and evaluate the differences between sprinters and middle-distance runners. Equipment and methods: Twenty-eight sprinters and twenty middle-distance runners took part in this study. All athletes were subject to four bipodal and monopodal stabilometries during the indoor-season: Pres.: pre-season; Volume: volume period; Precomp.: pre-competitive period; and Comp.: competitive period. Results: Analysis of variance (P < 0.05) showed main time effects in length and area of bipodal support, in length of left-side monopodal support and in length, area and speed of right-side monopodal support. Generally, athletes showed higher values in Volume than in Pres., in Volume than in Precomp. and in Precomp. than in Comp. Furthermore, main group effects were found in the anteroposterior stability of both monopodal supports, which displayed worse values for middle-distance runners. Conclusion: Our results suggest that athletes have worse postural stability in training periods with a higher volume of workload, and then improve in periods with a low-volume, high-intensity workload, without any influence from the athletic variety on these differences. However, sprinters display better monopodal stabilometry values regardless of the leg stance measured.